A prospective, multi-center, practice-based cohort study on all-ceramic crowns. Issue 8 (August 2021) - Wierichs, R.J.; Kramer, E.J.; Reiss, B.; Schwendicke, F.; Krois, J.; Meyer-Lueckel, H.; Wolf, T.G.
Highlights: For all-ceramic crowns high success rates (95%) could be found after up to 15years. Hybrid ceramics showed a 3.2times higher failure rate than feldspathic porcelain. Single-step adhesives showed 2.2times higher failure rate than multi-step adhesives. After the use of a composite liner the failure rate increased. The use of oxygen-blocking gels & sono abrasion techniques increased failure rates. Abstract: Objectives: The aim of this prospective, multi-center, practice-based cohort study was to analyze factors associated with the success of all-ceramic crowns. Methods: All-ceramic crowns placed in a practice-based research network ([Ceramic Success Analysis, AG Keramik) were analyzed. Data from 1254 patients with (mostly in-office CAD/CAM) all-ceramic crowns placed by 101 dentists being followed up for more than 5 years were evaluated. At the last follow-up visit crowns were considered as successful (not failed) if they were sufficient, whereas crowns were considered as survived (not lost) if they were still in function. Multi-level Cox proportional hazards models were used to evaluate the association between a range of predictors and time of success or survival. Results: Within a mean follow-up period (SD) of 7.2(2)years [maximum:15years] 776 crowns were considered successful (annual failure rate[AFR]:8.4%) and 1041 crowns survived (AFR:4.9%). The presence of a post in endodontically treated teeth resulted in a risk for failure 2.7 times lower than that of restorations without a post (95%CI:1.4–5.0;p = 0.002). Regarding the restorative material and adhesive technique, hybrid composite ceramics and single-step adhesives showed a 3.4 and 2.2 times higher failure rate than feldspathic porcelain and multi-step adhesives, respectively (p < 0.001). Use of an oxygen-blocking gel as well as an EVA instrument resulted in a 1.5–1.8 times higher failure rate than their non-use (p ≤ 0.001). Significance: After up to 15years AFR were rather high for all-ceramic crowns. Operative factors, but no patient- or tooth-level factors were significantly associated with failure. The study was registered in the German Clinical Trials Register (DRKS-ID: DRKS00020271).